2010
DOI: 10.1627/jpi.53.12
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of SnP<sub>2</sub>O<sub>7</sub>-based Proton Conductors to Intermediate-temperature Fuel Cells

Abstract: Much attention has been devoted to efforts to operate polymer electrolyte fuel cells (PEFCs) at temperatures above 100℃ in order to avoid the problem of serious CO poisoning of the anode catalyst. It is also of great con cern to operate PEFCs under low-humidity conditions, because the space and energy required for external humidi fication are eliminated or minimized in the fuel cell system. Thus, proton-conducting materials that can satisfy the above criteria have been proposed, developed, and evaluated worldw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Nagao et al reported that the conductivities of AP 2 O 7 (A = Sn, Ti, Ge, Si) increased in the order of Ge 4+ < Si 4+ < Ti 4+ < Sn 4+ in unhumidified air [9], and that proton-conducting Sn 1−x R x P 2 O 7 (R = Al 3+ , In 3+ ) were also applied to some electrochemical reactors, such as H 2 /air fuel cell, selective catalytic reduction of NO x , direct oxidation of methane to methanol, and gas sensors, etc. [13][14][15][16][17][18]. Chen et al reported that Sn 0.9 In 0.1 P 2 O 7 can conduct both protons and oxide-ions in the temperature range from 403 to 503 K [19].…”
Section: Introductionmentioning
confidence: 99%
“…Nagao et al reported that the conductivities of AP 2 O 7 (A = Sn, Ti, Ge, Si) increased in the order of Ge 4+ < Si 4+ < Ti 4+ < Sn 4+ in unhumidified air [9], and that proton-conducting Sn 1−x R x P 2 O 7 (R = Al 3+ , In 3+ ) were also applied to some electrochemical reactors, such as H 2 /air fuel cell, selective catalytic reduction of NO x , direct oxidation of methane to methanol, and gas sensors, etc. [13][14][15][16][17][18]. Chen et al reported that Sn 0.9 In 0.1 P 2 O 7 can conduct both protons and oxide-ions in the temperature range from 403 to 503 K [19].…”
Section: Introductionmentioning
confidence: 99%
“…at intermediate temperatures (373-573 K) [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Hibino et al reported that SnP 2 O 7 and Sn 0.9 In 0.1-P 2 O 7 exhibit high protonic conductivities of above 10 − 2 S cm − 1 from 348 to 573 K and above 10 − 1 S cm − 1 from 398 to 573 K under unhumidified conditions, respectively [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Polymer electrolytes are not applicable in ITFCs due to their dehydration or chemical degradation at temperatures above 100 • C, causing low conductivity or system deterioration. 8,9 Thus, inorganic electrolytes are needed for fuel cells operating at these intermediate temperatures. As most of the inorganic conductors exhibit very low conductivity at temperatures below 1000 • C, 10 to find electrolytes with promising conductivity at temperatures between 200-600 • C is crucial to the development and commercialization of ITFCs.…”
mentioning
confidence: 99%